2002
DOI: 10.1111/1467-8306.00277
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns and Determinants of Winter Atmospheric Carbon Dioxide Concentrations in an Urban Environment

Abstract: The purpose of this article is to describe determinants and spatial patterns of atmospheric carbon dioxide (CO 2 ) in Phoenix, Arizona. Specifically, we use geographic information systems (GIS) and regression-based analyses to identify the human and biological factors that contribute to spatial and temporal variations in near-surface (2-meter height) atmospheric CO 2 levels. We use these factors to create estimated surfaces of CO 2 concentrations for the area. We evaluate the surfaces using records of CO 2 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Few intercomparisons have been performed between urban and rural CO 2 levels (Widory and Javoy 2003;George et al 2007;Pataki et al 2007;Rice and Bostrom 2011) and differences have been found. Wentz et al (2002) illustrate the results obtained in some studies.…”
Section: Introductionmentioning
confidence: 84%
“…Few intercomparisons have been performed between urban and rural CO 2 levels (Widory and Javoy 2003;George et al 2007;Pataki et al 2007;Rice and Bostrom 2011) and differences have been found. Wentz et al (2002) illustrate the results obtained in some studies.…”
Section: Introductionmentioning
confidence: 84%
“…MOPITT measurements of CO combined with the WRF-Chem climate model, before and during the Beijing Olympics suggest that reductions in urban emissions could be met from urban traffic controls [68]. Indirect air quality modeling efforts also rely on remotely sensed data sources, in conjunction with NDVI and land use data as inputs to a regression model that maps atmospheric gases including nitric oxide, nitrogen dioxide, and nitrogen oxides, and carbon dioxide in urban areas [69,70].…”
Section: Air Qualitymentioning
confidence: 99%
“…Several studies highlighted the fact that the CO 2 concentrations measured in and around cities are directly sensitive to factors that control the CO 2 fluxes: proximity to urban centers and industrial sources, ground and air traffic, vegetation distribution and rates of primary productivity (e.g., Wentz et al, 2002;Grimmond et al, 2002;Apadula et al, 2003;Nasrallah et al, 2003;Gratani and Varone, 2005;Strong et al, 2011). Furthermore, advection and vertical mixing strongly influence the urban CO 2 signal (e.g., Idso et al, 2002;Moriwaki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%